PANDANGAN ABDURRAHMAN WAHID TENTANG PLURALISME DALAM ISLAM: KAJIAN HADIS TEMATIK DI ERA KONTEMPORER - Ajir, Muhajirin; Zulfahmi Alwi; Arifuddin Ahmad (Istiqra: jurnal hasil penelitian, 2025)
This study examines Abdurrahman Wahid’s views on pluralism in Islam through a thematic hadith approach. Using a qualitative literature method, it analyzes Wahid’s thoughts and relevant hadith texts. The findings show that Wahid sees pluralism as an essential Islamic teaching that promotes respect for diversity and fair treatment without discrimination. He emphasized religious freedom as a fundamental human right, aligning with la ikraha fid-din (no compulsion in religion). Wahid also advocated for protecting non-Muslim rights and fostering equality by interpreting Islam inclusively as rahmatan lil ’alamin (a blessing for the universe). His initiatives, such as recognizing Confucianism as an official religion in Indonesia, aimed at building a tolerant society. Wahid connected pluralism with universal values like justice, compassion, and brotherhood (ukhuwah insaniyah), rejecting exclusivism and urging Muslims to prioritize shared human values over religious differences. The novelty of this study lies in its thematic hadith analysis of Wahid’s pluralism, revealing how Islamic teachings support religious freedom, justice, and equality. It also highlights the application of these values in Indonesia’s social policies and discourse. The findings recommend strengthening inclusive Islamic discourse in education and da’wah to instill pluralism. Additionally, social policies should further protect minority rights and enhance regulations promoting justice and equality, fostering harmony in a multicultural society.